Construction of Social In The News Watch Out There Is A Muri Record Hoax For Prabowo Ahead of The Presidential Election In Indonesia 2024 - Dwinarko, Dwinarko; Muhamad, Pagi; Reza, Fikri (Dinasti Research, 2024)
Online mass media coverage is a media organization strategy in placing campaign framing on the presidential debate, and vice president, in 2024 aimed at the wider community, simultaneously and simultaneously. The purpose of this research is to find out the Social Construction of Democracy in Framing the News of Awarding Muri Records in Online Media in the Presidential Election Process in Indonesia in 2024. The theory used is Framing theory with qualitative research methods with online news text analysis in the news period November 28, 2023 and scheduled to end on February 10, 2024, samples of online media coverage of the Muri record as part of the framing analysis unit. The research findings that framing is a strategy of organizations, individual journalists and media coverage in presenting news. Framing is a reality construction that explains the conditions of democracy and socio-cultural conditions, and public knowledge by interpreting the reality of democracy as part of the implementation of public participation in determining the choice of president and vice president. Frames organize principles that are socially shared and persistent over time, work symbolically and meaningfully on the structure of the social world. Frames thus (1) serve to organize information and (2) accomplish this by providing an identifiable pattern or structure of various complexities. They (3) are based on abstract principles and ideas and (4) are consequently visible in symbolic forms of expression. To be functional, frames (5) must be shared (at least at some level) by members of a particular group or society and (6) persistent - their value lies in their durability, persistence and routinization over longer periods of time. The urgency of the research is that the framing model encourages journalists' reporting creativity in presenting online news. Research recommendations, creativity can function in shaping the organization of news that is integrated in macro, messo and micro news with the vision and mission of the media organization.